Visual Representation of Environmental Awareness in Sampoerna A Mild Advertisement - Ismaya, Ariel Khidir; Ade Mulyanah (BRIN Publishing (Penerbit BRIN), 2024)
The research is to describe the visual representation of environmental awareness in Sampoerna, a mild advertisement. It is about advertising serving as an effective medium for conveying messages to the public, including issues related to environmental awareness. Sampoerna A Mild, a well-known cigarette brand recognized for its creative and often ironic advertising approach, utilizes strong visual elements and symbolism to communicate various social messages. This study examines the visual representation of environmental awareness in Sampoerna A Mild advertisements by employing multimodal analysis from Kress and Van Leeuwen (1996;2026) taken from the semiotic theory from Roland Barthes and visual rhetoric theory to analyze the meaning behind visual elements and their impact on audience perception. The research uses qualitative content analysis to explore selected advertisements, focusing on colours, symbols, imagery, and linguistic elements. The findings reveal that Sampoerna A Mild advertisements frequently incorporate irony, humour, and wordplay, subtly embedding environmental awareness within their messaging. Visual elements such as natural landscapes, green tones, and the contrast between pollution and nature are commonly used to create an indirect commentary on environmental issues. Additionally, the paradoxical relationship between smoking and sustainability is evident, reflecting a nuanced engagement with ecological themes rather than an explicit advocacy for environmental activism. This study highlights how the cigarette industry incorporates environmental discourse into its marketing strategies and influences public perception.